From tablet to table: How augmented reality influences food desirability - Fritz, William; Hadi, Rhonda; Stephen, Andrew (Journal of the Academy of Marketing Science, 2023)
Abstract Augmented reality (AR) technology has generated enormous industry investment and buzz, with the food and beverage sector quickly embracing this technology in an effort to enhance the customer experience. However, academic research has only just begun to empirically explore how and why this technology might influence consumer judgements and behaviors in such contexts. Across two field studies involving consequential behavior and two controlled laboratory studies, we find that AR’s unique ability to visually superimpose objects onto a real-time environment increases consumers’ ability to mentally simulate consuming a pictured food, which in turn increases their desire and purchase likelihood of the food item. Further, we find the increased mental simulation produced by AR is itself preceded and driven by an increased sense of personal relevance of the food items.